Interactions between spirometry and oscillometry in patients with moderate to severe asthma. Issue 4 (13th October 2022) - Chan, Rory; Lipworth, Brian
Small airways dysfunction defined by spirometry and oscillometry together confers worse outcomes in moderate to severe asthma. This emphasises the importance of combining spirometry and oscillometry to characterise the small airway asthma phenotype. https://bit.ly/3CcaZ3e